Livestock and range research in Botswana 1986 - Ministry of Agriculture, Botswana (1987)
Observational study was conducted to determine the genetic potential of the Tswana goats for milk production and to determine production parameters of the goats under traditional management in Tutume agricultural district in northeastern Botswana between January and December 1986. Results indicated overall kidding rate of 137% with litter size 1.37. Mean birth weight of single borns females, single born males, twin born females and twin born males were 3.6±0.9, 4.3±1.5,3.7±1.0kg, and 4.3±1.0kg respectively. Overall mean per goat daily milk production was 284 ml with highest average of 959 ml during November. At the end of rainy season mature females (n=159) had a mean weight of 38.8±5.0 kg while 3 mature females weighed 35.0±4.9 kg and six mature males weighed 39.7±8.2 kg. In addition, information is collected on herd structure, milk production per farmer and offtake and marketing of milk.